Effects of microRNA-181b-5p on cognitive deficits in first-episode patients with schizophrenia: Mediated by BCL-2. (April 2021) - Gou, Mengzhuang; Pan, Shujuan; Tong, Jinghui; Zhou, Yanfang; Han, Jiarui; Xie, Ting; Yu, Ting; Feng, Wei; Li, Yanli; Chen, Song; Cui, Yimin; Tian, Baopeng; et al.
Abstract: MicroRNA (miR)-181b-5p is considered to be involved in the pathogenesis of schizophrenia, and one of its regulatory target genes BCL-2 (B-cell lymphoma 2) is suggested to associate with cognition of schizophrenia. Cognitive deficit is a core trait of schizophrenia. However, it remains unclear whether miR-181b-5p affects cognition and its possible pathway in schizophrenia. We hypothesized that miR-181b-5p affects cognition by targeting BCL- 2 mRNA and downregulating BCL-2 protein expression in schizophrenia patients. In this study, first-episode patients with schizophrenia (FEPS, n = 123) and age- and gender-matched healthy controls (HCs, n = 50) were enrolled in Chinese populations. Expression levels of miR-181b-5p and BCL- 2 mRNA in peripheral whole blood were measured with quantitative real-time PCR (Q-PCR) and BCL-2 protein in plasma were measured with Enzyme Linked Immunosorbent Assay (ELISA). Psychopathology was assessed with the Positive and Negative Syndrome Scale (PANSS), cognitive function was evaluated using the MATRICS Consensus Cognitive Battery (MCCB). Peripheral blood miR-181b-5p expression level was significantly upregulated ( p = 0.001) whereas BCL- 2 mRNA and BCL-2 protein levels were significantly downregulated ( p = 0.002, p = 0.023 respectively) in the FEPS compared with those in the HCs. The miR-181b-5p level was negatively ( p = 0.005), whereas the BCL- 2 mRNA level was positively ( p < 0.001), correlated with working memory in FEPS. Mediating effect analysis showed that the effect of miR-181b-5p on working memory in the FEPS was exerted via targeting BCL- 2 mRNA. MiR-181b-5p in combination with BCL- 2 mRNA might be suggested as potential biomarker for schizophrenia in our discovery sample. In conclusion, overexpressed miR-181b-5p may affect cognitive function in patients with schizophrenia. Highlights: Overexpressed microRNA-181b-5p may affect working memory of schizophrenia patients. This effect was mediated by BCL- 2 mRNA in first-episode patients with schizophrenia. MicroRNA-181b-5p and BCL-2 mRNA have the potential to be a biomarker.